Vibrational analysis of microtubules embedded within viscoelastic medium using orthotropic Kelvin like model - Muhammad Safeer; Muhammad Taj (Penerbit Universiti Kebangsaan Malaysia, 2019)
Microtubules, the key components of cytoskeleton of all living cells, are important for maintaining the cell shape and transporting the cellular organelles. Understanding the mechanics of microtubules is very important for these functions. Mechanics of these components are greatly affected when they are embedded in cells. To understand the mechanical properties of microtubules in living cells, we developed an orthotropic-Kelvin like model and investigated the vibrational behavior when they are embedded in surrounding elastic medium. We considered them as orthotropic elastic shell and its surrounding elastic matrix as Kelvin model. We found that due to mechanical coupling of these components with the elastic medium, the flexural vibration is increased and radial frequencies in all modes are increased considerably while other vibrational modes are not affected that much.